2014
DOI: 10.4103/0970-4388.127059
|View full text |Cite
|
Sign up to set email alerts
|

To assess and create awareness among anesthetists regarding prevention and management of injuries to the teeth and their associated structures during general anesthesia

Abstract: Pediatric dentists can play a major role in creating the awareness among the anesthesia providers regarding prevention of oro-dental injuries during anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Tiku et al (10) reported that dental injuries and damage to corresponding dental structures occurred during laryngoscopy procedures in 96% of their study participants; 2% reported that injuries occurred during endotracheal intubation, and 2% noted that airway removal was the cause of dental trauma. These findings are consistent with the present results, which indicate that the main culprit is laryngoscopy technique, followed by use of incorrect operative technique.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tiku et al (10) reported that dental injuries and damage to corresponding dental structures occurred during laryngoscopy procedures in 96% of their study participants; 2% reported that injuries occurred during endotracheal intubation, and 2% noted that airway removal was the cause of dental trauma. These findings are consistent with the present results, which indicate that the main culprit is laryngoscopy technique, followed by use of incorrect operative technique.…”
Section: Discussionmentioning
confidence: 99%
“…Litigation risk can be substantially reduced be fully disclosing possible trauma risks to the patient or person responsible for the patient and by having them sign all necessary waivers (4,10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations